2018
DOI: 10.1016/j.matchar.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser rescanning on the grain microstructure of a selective laser melted Al-Mg-Zr alloy

Abstract: The microstructures of alloys created via Additive Manufacturing (AM) can vary substantially from those present in cast or wrought products, due to the very rapid solidification associated with AM.While numerous studies have investigated the process-microstructure relationship of alloys created by Selective Laser Melting (SLM), few have investigated the effects of laser rescanning to alter the microstructure or take advantage of the rapid solidification conditions the process provides. This study investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(78 citation statements)
references
References 36 publications
4
61
0
1
Order By: Relevance
“…A similar bimodal microstructure was observed by Griffiths et al in Sc-free Al-Mg-Zr (Addalloy TM ) LPBF samples [77]. The authors focused the attention on the effect of laser rescanning on the microstructure of Addalloy TM observing a refinement of the microstructure thanks to the remelting of columnar grains and the precipitation of Al 3 Zr seeds.…”
Section: Aluminum Alloys For Lpbfsupporting
confidence: 66%
“…A similar bimodal microstructure was observed by Griffiths et al in Sc-free Al-Mg-Zr (Addalloy TM ) LPBF samples [77]. The authors focused the attention on the effect of laser rescanning on the microstructure of Addalloy TM observing a refinement of the microstructure thanks to the remelting of columnar grains and the precipitation of Al 3 Zr seeds.…”
Section: Aluminum Alloys For Lpbfsupporting
confidence: 66%
“…The high‐temperature fluids with a low density inevitably rose; on the contrary, the low‐temperature fluids with a high density sank, which leads to convection of fluids in the molten pool . The heat flow remelts the previously formed columnar crystals and triggers them to peel off . The detached grains are engulfed into the molten pool and formed free grains, which may become the source of crystal nuclei in fine‐grain zone (FGZ).…”
Section: Resultsmentioning
confidence: 99%
“…The detached grains are engulfed into the molten pool and formed free grains, which may become the source of crystal nuclei in fine‐grain zone (FGZ). Additional heating from laser rementing can also influence the grain microstructure . The remelted microstructures, which are taken from horizontal surfaces of tungsten, are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the remelting strategy in SLM improves the surface quality and relative density. Griffiths et al [ 21 ] found that because of the reduced laser energy absorption and increased heat losses in the solid, the laser rescanning reduced the amount of columnar grains and increased the number of equiaxed grains. Xiao et al [ 22 ] studied the effect of the rescanning cycle on the relative density, microstructure, residual stress, and mechanical properties of SLMed Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%